Bounding of correlated double-differenced GNSS observation errors using NRTK for precise positioning of autonomous vehicles - Elsayed, Hassan; El-Mowafy, Ahmed; Wang, Kan (ELSEVIER SCI LTD, 2023)
Bounding satellites’ nominal measurement errors to calculate the protection level (PL) of the position error is a salient step of integrity monitoring of positioning autonomous vehicles (AVs). In this work, the focus is on applying the network RTK approach which is a suitable technique for precise positioning of AVs. A measurement weighting matrix formed from the overbounding standard deviation (STD) and considers the correlation among differenced observations was developed to achieve conservative PLs. Two approaches were designed to estimate the overbounding parameters and compute the correlation coefficients using one full year of different satellites measurements from multiple constellations. The Two-Step Gaussian Bounding method is used to calculate the overbounding parameters. The overbounding mean and STD of both code and phase observation errors for both approaches were in the range of 0.0003–1.369 m and 0.007–2.497 m, respectively. While the first approach provides a tight overbounding results, the second is more conservative.